Konsep Permohonan Keputusan Fiktif Positif Pasca Berlakunya Pasal 175 Angka 7 Undang-Undang Nomor 6 Tahun 2023 Tentang Penetapan Peraturan Pengganti Undang-Undang Nomor 2 Tahun 2022 Tentang Cipta Kerja - Nur Eka Fatimatuz Zahro; Ahmad Hasan Basri (Journal of Law and Islamic Law, 2023)
This paper examines applying for a favorable fictitious decision after the entry into force of Article 175 Number 7 of Law Number 6 of 2023 concerning the Stipulation of Government Regulation instead of Law Number 2 of 2022 concerning Job Creation (Job Creation Law). The PTUN's authority to examine, adjudicate and decide on positive fictitious applications is eliminated or replaced. Its authority will be further regulated in a presidential regulation, but until now, a presidential regulation has yet to be issued, resulting in legal uncertainty or a legal vacuum. The type of research used is normative, and the research approach uses a statutory approach (statute approach), conceptual approach (conceptual approach), and case approach (case approach). Research results After the entry into force of the Job Creation Law, the concept of a positive fictitious decision application underwent its main change, namely removing the authority of the State Administrative Court (PTUN) to grant it legally because judges may accept a case claimed by the applicant. It can be filed through a factual action lawsuit because government agencies or officials have violated the general principles of good governance. Article 175 of Law number 7 Job Creation which regulates fictitious applications, does not fulfill the elements of legal certainty, namely: the first element in the law still creates multiple interpretations, the second element, if the Administrative Court's authority is removed, it will not be under the principle of checks and balances